2011
DOI: 10.1371/journal.pone.0019872
|View full text |Cite
|
Sign up to set email alerts
|

Severe and Persistent Depletion of Circulating Plasmacytoid Dendritic Cells in Patients with 2009 Pandemic H1N1 Infection

Abstract: BackgroundDysregulation of host immune responses plays a critical role in the pathogenesis of severe 2009 pandemic H1N1 infection. Whether H1N1 virus could escape innate immune defense in vivo remains to be investigated. The aim of this study was to evaluate the pattern of innate immune response during human 2009 H1N1 infection. We performed the enumeration of circulating myeloid dendritic cells (mDC) and plasmacytoid DC (pDC) in blood from patients with H1N1 pneumonia shortly after the onset of symptoms and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
2
26
2
Order By: Relevance
“…CCL‐5/RANTES is a known mediator of inflammation . Contrary to our study, another study which measured plasma levels of CCL‐5/RANTES in A (H1N1) pdm09 did not show lower levels of CCL‐5/RANTES when compared to healthy controls . However, CCL‐5/RANTES levels were reported to be slightly lower in (H1N1) pdm09 and seasonal H3 infection earlier during the infection and was shown to be increased during the recovery period .…”
Section: Discussioncontrasting
confidence: 99%
“…CCL‐5/RANTES is a known mediator of inflammation . Contrary to our study, another study which measured plasma levels of CCL‐5/RANTES in A (H1N1) pdm09 did not show lower levels of CCL‐5/RANTES when compared to healthy controls . However, CCL‐5/RANTES levels were reported to be slightly lower in (H1N1) pdm09 and seasonal H3 infection earlier during the infection and was shown to be increased during the recovery period .…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, this is the first report to describe decreased blood myeloid DC subsets following vaccination in humans, however transient decreases in blood myeloid DCs have been observed in other conditions: 1) during acute myocardial infarction, where it is suggested that they are being recruited into the vessel wall and accumulating in atherosclerotic plaques (1822), 2) in burn patients where it is associated with the incidence of sepsis (23), and 3) during acute viral infections including CMV (24) and pandemic H1N1 influenza (25). Additionally, following injection of the TLR7/8 agonist R-848 or the TLR9 agonist CpG-ODN in rhesus macaques, a decline in mDC were observed (26).…”
Section: Discussionmentioning
confidence: 99%
“…Number of circulating DCs is reported to decrease in infection of certain viruses such as influenza H1N1 virus [17], cytomegalovirus [18], and dengue virus [19]. Because clinical picture of Kawasaki disease, including hematological and blood chemistry data, is not compatible with these known viral infections, these viruses should not take etiological role.…”
Section: Discussionmentioning
confidence: 99%
“…Immature DCs are activated after the capture of antigens in circulation or affected tissues, and then the activated DCs migrate through lymphatic vessels to lymphoid organs where they present processed antigens to naïve T cells [7][8][9][10]. Abnormalities of DC homeostasis have been involved in the pathophysiology of various human diseases, including autoimmune diseases [11][12][13][14][15], ischemic heart disease [16], and viral infection [17][18][19].…”
Section: Introductionmentioning
confidence: 99%